Antibiotic resistances of enterococci isolated from bovine subclinical mastitis - Yahya Kuyucuoğlu (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to investigate the antibiotic resistances of enterococci species isolated from bovine subclinical mastitis in dairy cows. Materials and Methods: A total of 392 CMT positive milk samples were collected from dairy farms in Afyonkarahisar. Typing of enterococcus species were performed using API 20 Strep, subsequently, antibiotic sensitivities were determined by disk diffusion method according to the National Committee for Clinical Laboratory Standards. Results: A total of 43 isolated enterococci, involved in bovine mastitis. The majority of isolates were E. faecalis (53.4%), followed by E. faecium (18.6%). The remaining 12 (27.9%) strains could not be classified. This study observed that the highest percentage of resistance by E. faecalis were to tetracycline (91.3%), erythromycin (82.6%) and penicillin (78.2%). Conclusion: This study showed a high prevalence of antimicrobial resistant E. faecalis, E. faecium and other Enterococci species isolated from CMT positive milk samples. Resistance to antibiotics in enterococci is becoming a concern for human and environmental health.